La démocratie britannique face au modèle parlementaire écossais - Nathalie DUCLOS (E-REA)
British democracy faced with the Scottish parliamentary modelLike other great democracies, the UK has been under attack since at least the 1980s from constitutional reformers who have pointed out the limits of representative democracy and of the British model of majoritarian democracy (or “Westminster model”). It is in this context that the new Scottish parliamentary model was imagined. The creation of a Scottish Parliament in 1999 was seen as a unique opportunity to put into practice the “new politics” which groups such as Charter88 were advocating. It was hoped that the Scottish Parliament could then serve as a “model for democracy”, and at the very least as a model for the Westminster Parliament. Ten years after the establishment of the Scottish Parliament, this article aims at establishing whether British MPs have taken an interest in the procedural novelties tried out in Edinburgh and to what extent the Scottish Parliament has had an institutional influence over Westminster. It concludes that the creation of the Scottish Parliament has only had a marginal effect on Westminster and explores several possible reasons for Westminster’s unwillingness to reform.